VD_FINDINFO AI 294/18 - 174/2019 vom 7. Juni 2019 - VD Tribunal cantonal (2019)
CARCINOME, DÉPRESSION, EXPERTISE MÉDICALE, MAXIME INQUISITOIRE | 28a al. 1 LAI, 29 al. 1 LAI, 4 al. 1 LAI, 43 LPGA, 44 LPGA, 6 LPGA, 61 let. c LPGA, 7 LPGA, 8 LPGA